Non revenue water (NRW) Sg. Lembing experienced - Ahmad Wafi Zaim, Kharudin (2012)
Water losses are one of the main problems that occur in water distribution network. Malaysia as a developing country is also exceptional to the same problem. Water leakage contributes to the nature sources losses and gives big impact to our country in terms of economic growth. Non Revenue Water (NRW) occurs is due to leakage in main water distribution, error on distribution meter and other losses. According to an investigation done in 2002 by the Malaysia Water Association (MW A), the total amount of losses in NRW due to leakage is approximated between in the range of 16 to 30% from total amount of water production. As matter of fact, a NRW reduction programme should be conducted in order to supply population water demand. To overcome financial losses, an effort of NR W monitoring needs full responsibility and commitment as priority in department of water authorities. In this case study at Sg.Lembing Pahang, NRW is determined based on the differences of volumes between system input volume and billed authorization consumption Besides that, comparison of current leakage percentage in the water system between zones is conducted to analysis factors that influence leakage rate and NRW level. Thus, the results obtained from this study could provide useful information to overcome water leakage problems and design better water distribution system modeling.